Disseminating a Smoke-free Homes Program to Low Socioeconomic Status Households in the United States Through 2-1-1: Results of a National Impact Evaluation. Issue 4 (12th May 2018) - Bundy, Łucja T; Haardörfer, Regine; Kegler, Michelle C; Owolabi, Shadé; Berg, Carla J; Escoffery, Cam; Thompson, Tess; Mullen, Patricia Dolan; Williams, Rebecca; Hovell, Mel; Kahl, Tanya; Harvey, Dayanne; et al.
Abstract: Introduction: Given homes are now a primary source of secondhand smoke (SHS) exposure in the United States, research-tested interventions that promote smoke-free homes should be evaluated in real-world settings to build the evidence base for dissemination. This study describes outcome evaluation results from a dissemination and implementation study of a research-tested program to increase smoke-free home rules through US 2-1-1 helplines. Methods: Five 2-1-1 organizations, chosen through a competitive application process, were awarded grants of up to $70 000. 2-1-1 staff recruited participants, delivered the intervention, and evaluated the program. 2-1-1 clients who were recruited into the program allowed smoking in the home, lived in households with both a smoker and a nonsmoker or child, spoke English, and were at least 18 years old. Self-reported outcomes were assessed using a pre-post design, with follow-up at 2 months post baseline. Results: A total of 2345 households (335–605 per 2-1-1 center) were enrolled by 2-1-1 staff. Most participants were female (82%) and smokers (76%), and half were African American (54%). Overall, 40.1% ( n = 940) reported creating a full household smoking ban. Among the nonsmoking adults reached at follow-up ( n = 389), days of SHS exposure in the past week decreased from 4.9 (SD = 2.52) to 1.2 (SD = 2.20). Among the 1148 smokers reached for follow-up, 211 people quit, an absolute reduction in smoking of 18.4% ( p < .0001), with no differences by gender. Conclusions: Among those reached for 2-month follow-up, the proportion who reported establishing a smoke-free home was comparable to or higher than smoke-free home rates in the prior controlled research studies. Implications: Dissemination of this brief research-tested intervention via a national grants program with support from university staff to five 2-1-1 centers increased home smoking bans, decreased SHS exposure, and increased cessation rates. Although the program delivery capacity demonstrated by these competitively selected 2-1-1s may not generalize to the broader 2-1-1 network in the United States, or social service agencies outside of the United States, partnering with 2-1-1s may be a promising avenue for large-scale dissemination of this smoke-free homes program and other public health programs to low socioeconomic status populations in the United States.